PENGARUH IMBALAN INTRINSIK TERHADAP SIKAP PEGAWAI YANG DIMEDIASI OLEH PERSEPSI DUKUNGAN ORGANISASI - Ismail, Ismail; Suryani, Irma (J-MIND (Jurnal Manajemen Indonesia), 2021)
This study aims to examine the effect of Intrinsic Rewards on Employee Attitudes mediated by Perceptions of Organizational Support at the Social Service of Gayo Lues Regency. The sampling method in this research uses sensus sampling with a sample of 115 respondents. The results of this study indicate that the variables of intrinsic reward and perceived organizational support have a significant effect on employee attitudes. Furthermore, the perceived organizational support variable partially mediates the intrinsic rewards of employee attitudes.